2008
DOI: 10.1007/s11571-008-9054-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired associative learning in schizophrenia: behavioral and computational studies

Abstract: Associative learning is a central building block of human cognition and in large part depends on mechanisms of synaptic plasticity, memory capacity and fronto-hippocampal interactions. A disorder like schizophrenia is thought to be characterized by altered plasticity, and impaired frontal and hippocampal function. Understanding the expression of this dysfunction through appropriate experimental studies, and understanding the processes that may give rise to impaired behavior through biologically plausible compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 84 publications
3
35
0
Order By: Relevance
“…Learning related deficits are also a hallmark of the schizophrenia diathesis (Diwadkar et al, 2008) and have been linked to deficits in visuo-spatial memory as well (Wood et al, 2002). In general, working memory and executive processes may be central to several cognitive domains including associative learning, which does rely on the temporary maintenance of memoranda (relying on frontal activity) before items can be consolidated in longer-term memory (Bunge et al, 2004; Ranganath et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Learning related deficits are also a hallmark of the schizophrenia diathesis (Diwadkar et al, 2008) and have been linked to deficits in visuo-spatial memory as well (Wood et al, 2002). In general, working memory and executive processes may be central to several cognitive domains including associative learning, which does rely on the temporary maintenance of memoranda (relying on frontal activity) before items can be consolidated in longer-term memory (Bunge et al, 2004; Ranganath et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous fMRI studies have shown that the task strongly modulates responses in the hippocampus, as well as effective connectivity between the hippocampus and neo-cortical regions (Banyai et al, 2011; Buchel et al, 1999; Woodcock et al, 2016; Woodcock et al, 2015). Moreover, behavioral proficiency on the task has been shown to conform to classic mechanisms of negatively accelerated learning (Diwadkar et al, 2016; Diwadkar et al, 2008), suggesting that the task characteristics strongly engage basic hippocampal mechanisms of learning and memory (Hasselmo, 1999; Rolls, 1996). …”
Section: Methodsmentioning
confidence: 99%
“…The course of paired-associate learning is well approximated by functions with a negatively accelerated or sigmoidal growth behavior, with limited free parameters estimating learning rate (Diwadkar et al, 2008). The dynamics of the task thus permits cleavage into sub-groups of relatively fast and slow learners based on the fitted response functions, and task performance has been linked to estimated fMRI metrics.…”
Section: Introductionmentioning
confidence: 99%
“…There are successful computational models of mental diseases, for instance of impaired associative learning in schizophrenia (Diwadkar et al 2008) or sleep disturbance in autism (Matsuura et al 2008) or other disorders (Reggia et al 1999). However, these models should be taken one step further as recent genetic studies show that serious mental diseases manifested as compromised cognitive and/ or affective status are thought to be linked to mutations of genes.…”
Section: Discussionmentioning
confidence: 99%